1992
DOI: 10.1063/1.108221
|View full text |Cite
|
Sign up to set email alerts
|

Interface roughness scattering in InAs/AlSb quantum wells

Abstract: We present a study of interface roughness scattering in not-intentionally-doped AlSb/InAs/AlSb quantum wells grown by molecular beam epitaxy on [001] GaAs semi-insulating substrates. The low-temperature mobility is found to be limited by interface roughness scattering for well widths below 100 Å. The measured mobilities are well accounted for by Gold’s theoretical treatment [A. Gold, Phys. Rev. B 35, 723 (1987)], once it is suitably modified to account for the band nonparabolicity of InAs. The experimental ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 14 publications
6
42
0
4
Order By: Relevance
“…The functional dependence of mobility on density for sample C was found to be singularly dependent on interface roughness scattering, with fluctuation height Δ 2.7 and in-plane correlation length Λ 9 nm, similar to previously reported values 25 . Having assumed the same interface roughness parameters apply to sample A and B, it was found that including alloy heterostructures.…”
Section: Manuscriptsupporting
confidence: 72%
“…The functional dependence of mobility on density for sample C was found to be singularly dependent on interface roughness scattering, with fluctuation height Δ 2.7 and in-plane correlation length Λ 9 nm, similar to previously reported values 25 . Having assumed the same interface roughness parameters apply to sample A and B, it was found that including alloy heterostructures.…”
Section: Manuscriptsupporting
confidence: 72%
“…As the channel thickness increases, the maximum of the wave function of electrons is displaced away from the upper interface of the QW, reducing the interactions of electrons with remote donor impurities. As demonstrated by Bolognesi et al, 12 interface roughness scattering can also be significant at room temperature for thin QW on a metamorphic buffer. We measured by atomic force microscopy a root mean square roughness of about 5 nm on a 25 m 2 image ͓the surface exhibits height fluctuations of about 8 nm on a lateral scale of about 500 nm ͑Ref.…”
Section: Discussionmentioning
confidence: 75%
“…Bolognesi et al [8] demonstrated that interface roughness is a key parameter limiting the low-temperature mobility of electrons in AlSb/InAs 2 DEG. Kroemer's group has also shown that the roughness is different using an AlSb or a GaSb buffer grown on a GaAs substrate [3].…”
Section: Results Ofmentioning
confidence: 99%